The Effect of Aren Palm Fiber Particle Size on Wea - Jihan Pamungkas; Arthur Leiwakabessy; Cendy S. E. Tupamahu (CV. AFDIFAL MAJU BERKAH, 2025)
Brake lining is one of the important components in a motor vehicle that functions to slow or stop the speed of the vehicle. In its application, brake lining has good physical properties and characteristics and meets safety factors. The use of palm fiber powder composites as an alternative material for brake linings was investigated to replace the use of asbestos, which carries health risks due to exposure to hazardous substances. In addition to the composition of palm fiber powder, the particle size of palm fiber powder is also a factor that can affect the wear rate value of the brake lining material. Because particle size affects the physical and mechanical properties of the composite. This study aims to analyze the effect of palm fiber powder particle size on the wear rate of brake lining. Palm fiber powder is available in sizes 40 mesh, 50 mesh, and 60 mesh. The results showed that the highest wear rate was found at 40 mesh particle size with a value of 1.83 x 10-⁷ g/mm²-second, followed by 50 mesh at 1.36 x 10-⁷ g/mm²-second, and the lowest at 60 mesh with a value of 8.49 x 10-⁸ g/mm²-second. This study indicates that the particle size of palm fiber has an effect on the wear rate value, where smaller particle sizes tend to produce better bonds between the particles and the composite matrix, thereby reducing the wear rate.